Metformin Ameliorates Chronic Colitis-Related Intestinal Fibrosis via Inhibiting TGF-β1/Smad3 Signaling - Wang, Ying; Wang, Zhi; Yang, Huiping; Chen, Shuze; Zheng, Dekai; Liu, Xiuying; Jiang, Qinrui; Chen, Ye (Frontiers in Pharmacology, 2022)
Intestinal fibrosis is considered to be a chronic complication of inflammatory bowel disease (IBD) and seriously threatening human health. Effective medical therapies or preventive measures are desirable but currently unavailable. Metformin has been proved to have a satisfactory anti-inflammatory effects in ulcerative colitis (UC) patients. Whether metformin can ameliorate chronic colitis-related intestinal fibrosis and the possible mechanisms remain unclear. Here, we established colitis-related intestinal fibrosis in mice by repetitive administration of TNBS or DSS. Preventive and therapeutic administration of metformin to chronic TNBS or DSS colitis mice indicated that metformin significantly attenuated intestinal fibrosis by suppressing Smad3 phosphorylation. In vitro studies with human colon fibroblast cell line (CCD-18Co) and primary human intestinal fibroblast treated with TGF-β1 confirmed the anti-fibrotic function of metformin for fibroblast activation, proliferation and collagen production. Mechanistically, metformin particularly inhibited phosphorylation and nuclear translocation of Smad3 by blocking the interaction of Smad3 with TβRI. These findings suggest that metformin will be an attractive anti-fibrotic drug for intestinal fibrosis in future therapies.